Concepts, outils (et idées claires) pour enseigner le point de vue - Alain Rabatel (Cahiers de Narratologie)
This article, based on the pragma-enunciative theorisation of points of view, focuses on the analysis of points of view in narratives. It first highlights the complexity of the notion of point of view, and then discusses a number of epistemological repercussions in different scientific and artistic fields. Thirdly, it presents the linguistic characteristics of the various sources and forms of point of view; it illustrates each of the concepts useful for their didactisation by analysing a small number of examples, highlighting the link between the instructions provided by the text and the interpretative choices resulting from the readers' hypotheses. Finally, it concludes with a number of general considerations aimed at optimising the didactisation of the notion.